Conformity Through Fear: A Multimodal Critical Discourse Analysis of COVID-19 Information Adverts - Gill, Kyle A.; Lennon, Henry (CADAAD journal, 2022)
The UK Government has produced an array of televised information adverts or ‘campaigns’ to increase public awareness of COVID-19 and promote compliance with its subsequent policy. Research has shown that compliance with public health policy is influenced by fearful visual-verbal campaign messaging strategies, and that emotive representations of ‘risk’ aregenerally perceived to be more effective than non-emotive discourse. However, how the Government has semiotically constructed and utilised fear within their COVID-19 campaigns to nudge public compliance remains unexplored. Preliminary analysis of seventeen COVID-19 adverts revealed four sequential phases to the Government’s pandemic response: responsibility, management, mitigation, and reflection. An in-depth Multimodal Critical Discourse Analysis of four selected adverts (one screenshot per advert, per phase), revealed that fear was constructed using less conventional meaning potentials in favour of more implicit multimodal semiotic interactions. By portraying a ‘good’ pandemic subject as one who makes ‘moral’ and ‘rational’ decisions to comply with COVID-19 policy, pre-existing societal inequalities which might hinder compliance, particularly for the socioeconomically disadvantaged groups of society, were reduced and problematised. This raises ethical concerns over notions of ‘expertise’ and the ‘rationalising’ of ‘irrational’ lifestyles. Future research should further explore multimodal nudges in public health campaigns to hold producers accountable.